The Effect of Work - Family Conflict and Work Locus of Control on Accident-Proneness: The mediator role of stress - Reza KHANI JAZNI; Mohammad HOSSEIN VAZIRI; Amir Barkhordari (Shahid Sadoughi University of Medical Sciences, 2019)
Abstract Introduction: Human  factor can be regarded as the most important and basic factors to cause the occurrence of occupational accidents. The accident proneness of the staff is recognized as an intrinsic and integrated trait of occupational accidents. Therefore, identifying factors affecting this issue can effectively prevent the occurrence of occupational accidents. This study aimed to evaluate the effect of work-family conflict, work control center, and stress on accident proneness. Methods: This analytical and cross-sectional research was conducted in 2018 using structural equation modeling (SEM) with partial least square approach. In total, 225 employees with a history of accidents were selected using sample size determining method in SEM. Data were collected using four questionnaires of work-family conflict, work control center, occupational stress, and accident proneness. Data analysis was performed in SPSS version 23 and SMARTPLS3. Results: In this study, composite reliability (CR) was applied to determine the reliability of the research tools, which yielded an acceptable correlation above 0.7 for all variables. In addition, average variance extracted (AVE) was exploited to assess the validity of the questionnaire, which was above 0.5 and acceptable. Furthermore, divergent validity was evaluated and confirmed by the new criterion (HTMT). To evaluate the fit of the structural model, linearity criteria, significance of coefficients, R2, f2, and Q2 were applied, results of which were indicative of the proper fit of the model. In addition, results demonstrated that all assumptions of the research were significant with the exception of the theory of effect of work-family conflict on accident proneness. Conclusion: Recognizing the individuals prone to accidents, as well as the causes of occupational accidents are significantly important in control of industry incidents with sensitive occupations. According to the results of the study, individuals with internal control can be selected for high-stress occupations during the screening in the beginning of recruitment of employees. In addition, the organization's management can reduce the occupational stress of the staff by decreasing work-family conflict, which leads to the improvement of performance and safety of work of these individuals.